2018
DOI: 10.3390/en11010102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spatial Relationships between Key Strata on the Height of Mining-Induced Fracture Zone: A Case Study of Thick Coal Seam Mining

Abstract: Abstract:The behavior of the overburden of working face 20104 at the Wangjialing coal mine was investigated using borehole imaging. The measured height of the conductive fracture zone (CFZ) in the overburden, 148 m, is significantly different from the height that is predicted by an empirical formula. The spatial relationships between key strata (KS) required for their fracturing and their influence on the CFZ's height were analyzed. The results demonstrate that the spatial relationships between adjacent KS are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This structure provides a large amount of storage space for oxygen and gas, which easily causes coal fire disasters, gas explosions and other accidents [2][3][4][5][6][7]. The pore and fissure structure of overlying strata can also serve as a water inrush channel to induce coal mine water inrush accidents [8][9][10]. Therefore, the study of the porosity distribution law of overlying strata in a goaf can provide theoretical and technical guidance for the identification of hidden disaster-causing factors and the reuse of gas and water resources in coal mines [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This structure provides a large amount of storage space for oxygen and gas, which easily causes coal fire disasters, gas explosions and other accidents [2][3][4][5][6][7]. The pore and fissure structure of overlying strata can also serve as a water inrush channel to induce coal mine water inrush accidents [8][9][10]. Therefore, the study of the porosity distribution law of overlying strata in a goaf can provide theoretical and technical guidance for the identification of hidden disaster-causing factors and the reuse of gas and water resources in coal mines [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works were performed within the creation of various models of the layered roof deformation [4][5][6][7], with the use of numerical models [8,9] which were used for the determination of the law of distribution of dynamic soil cracks under the influence of overlying bedded structures [10,11]. That should be noted that the considerable research is connected with the use of the frame models [12][13][14][15], based on the use of beam-and-hinge structures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the physical similarity simulation and field surveys, Zhou et al [20] and Yao et al [21] determined the distribution law of dynamic ground cracks under the influence of overlying strata structure. Li et al [22] indicated that spatial relationships between key strata have influence on the height of mining-induced fracture zone. Liang et al [23] discussed the influence of different key strata structure types on strata behavior with large mining height.…”
Section: Introductionmentioning
confidence: 99%